Haematological Analysis of Common Carp (Cyprinus carpio), Gold Fish (Carassius auratus), Tilapia (Oreochromis mossambicus) and Stinging Catfish (Heteropneustes fossilis) spontaneously infected with Aeromonas hydrophila - M, Dhanaraj; M.A, Haniffa; R.C, Muthu; A.J, Arockiaraj; S.S, Raman; A.V, Singh (Malaysian Journal of Science, 2008)
Gram negative ubiquitous bacterium Aeromonas hydrophila was injected into four freshwater fish species: common carp Cyprinus carpio, gold fish Carassius auratus, tilapia Oreochromis mossambicus and stinging catfish Heteropneustes fossilis at the rate of 10â¶ cfu/ml intramuscularly. Dermomuscular lesions resulted in H. fossilis and C. auratus was severe where as in C. carpio and O. mossambicus it was less severe. The result of cumulative mortality was maximum (100%) in H. fossilis on day 21, followed by C. auratus (60%), C. carpio (45%) and O. mossambicus (10%) respectively. The hematological parameters viz., white blood cells (WBC), red blood cells (REC), haemoglobin (Hb) and phagocytic activity were monitored at days 0, 7, 14, and 21. WBC (10â´mmâ»Â³) showed a linear increase from day 0 to day 21 and it was statistically different at p < 0.05 level. RBC (10â¶ mmâ»Â³) exhibited a linear decrease from day 0 to 2 in C. carpio, C. auratus and H. fossilis, but in O. mossambicus it decreased from day 0 to day 7 and increased after 7 days and reached a high level on day 14 and then decreased again in day 21 reaching the count observed on Day 0. Hb content of C. carpio, C. auratus and H. fossilis were statistically significant (p < 0.05) but it was not statistically significant in O. mossambicus, since the measurement was not uniform like the other three species. The results of RBC measurement of O. mossambicus were also similar to the results of Hb. The phagocytic activity of C. carpio, C. auratus and H. fossilis increased significantly from day 0 to day 21 and it was statistically significant at p < 0.05 level, but in O. mossambicus, a slight fluctuation was noticed during the experimental period.